Autonomy-Supportive and Controlling Teaching in the Classroom: A Video-Based Case Study - Jingwen Jiang; Marja Vauras; Simone Volet; Anne-Elina Salo; Anu Kajamies (MDPI AG, 2019)
This study explored teachers’ autonomy-supportive and controlling behaviors through video-taped observation in the classroom. Four lessons by two teachers from a secondary school in Finland were videotaped and analyzed using a rigorous coding protocol. It was found that teachers employed both autonomy-supportive and controlling teaching during the same lesson, and even combined them in the same instructional sequence. This finding suggests the complexity of the use of autonomy support and control in the classroom, as well as their context-dependent aspects. The novel finding from this study was that teachers showed error tolerance and creativity to support students’ autonomy. Showing error tolerance and teaching creatively have not been investigated from the perspective of autonomy support in previous research. Furthermore, this study suggested that indirect control and its negative effects on students’ learning and well-being should arouse more concern in future research. Implications for teaching practice concerning supporting students’ autonomy have been provided.